Odpowiedzi

  • Użytkownik Zadane
2009-04-08T17:07:43+02:00
1a
3½x-2⅖y=1,1/*10
½y+6=0,4x/*10

35x-24y=11
5y+60=4x

35x-24y=11
5y=4x-60/5

35x-24y=11
y=⅘x-12

35x-24*(⅘x-12)=11
y=⅘x-12

35x-19⅕=11-288
y=⅘x-12

15⅘x=-277/15⅘
y=⅘x-12

x≈17,53
y=⅘*17,53-12

x=17,53
y=2,024

1b
5x=6y-6
3x+5y=3

5x-6y=-6/*(-3)
3x+5y=3/*5

-15x+18y=18
15x+25y=15

43y=33/43
y=33/44

5x-6y=-6/*5
3x+5y=3/*6

25x-30y=-30
18x+30y=18

43x=-12/43
x=-12/43

2.
3,
2⅖x-1⅓y=6/*15
2¾x+3=1½y-3/*4

51x-20y=90/*11
11x-6y=-24/*(-51)

561x-220y=990
-561x+306y=1224

86y=2214/86y=25 32/43

51x-20y=90/*6
11x-6y=-24/*(-20)

306x-120y=540
-220x+120y=480

86x=1020/86
x=11 37/510